The Impact of Remittances on the Development of Domestic Tourism in Ghana. A Mediating Role of Cultural Exchange. - Tackie, Michael Kojoe Amoah; Mensah, Thelma Frimpong; Awadzie, David Mensah (International Journal of Business, Management and Economics, 2024)
The primary aim of this research is to investigate the influence of remittance on local tourism development in Ghana. The study used a survey research approach to gather data from the DuBois Center and the diaspora African forum in Accra. Five hundred questionnaires were distributed; notably, 453 questionnaires were successfully retrieved, yielding a response rate of 90.6%. The study examined four hypotheses using partial least squares structural equation modeling (PLS-SEM). The results indicate that remittance positively and significantly impacts cultural exchange and local tourism development. Additionally, the findings suggest a positive relationship between cultural exchange and local tourism development, with cultural exchange mediating the association between remittance and regional tourism. Policymakers should invest in tourism infrastructure development, such as transportation networks and housing options, to maximize the benefits of remittances and cultural exchange. Collaboration between the public and private sectors can maximize the benefits of remittances and cultural exchange for local communities by fostering synergies in tourism development